'So just to go through the options…': patient choice in the telephone delivery of the NHS Improving Access to Psychological Therapies services. Issue 1 (22nd September 2020) - Irvine, Annie; Drew, Paul; Bower, Peter; Ardern, Kerry; Armitage, Christopher J; Barkham, Michael; Brooks, Helen; Connell, Janice; Faija, Cintia L; Gellatly, Judith; Rushton, Kelly; Welsh, Charlotte; et al.
Abstract: This article considers patient choice in mental healthcare services, specifically the ways that choice is enabled or constrained in patient–practitioner spoken interaction. Using the method of conversation analysis (CA), we examine the language used by practitioners when presenting treatment delivery options to patients entering the NHS Improving Access to Psychological Therapies (IAPT) service. Analysis of 66 recordings of telephone‐delivered IAPT assessment sessions revealed three patterns through which choice of treatment delivery mode was presented to patients: presenting a single delivery mode; incrementally presenting alternative delivery modes, in response to patient resistance; and parallel presentation of multiple delivery mode options. We show that a distinction should be made between (i) a choice to accept or reject the offer of a single option and (ii) a choice that is a selection from a range of options. We show that the three patterns identified are ordered in terms of patient‐centredness and shared decision‐making. Our findings contribute to sociological work on healthcare interactions that has identified variability in, and variable consequences for, the ways that patients and practitioners negotiate choice and shared decision‐making. Findings are discussed in relation to tensions between the political ideology of patient choice and practical service delivery constraints.